Effects of Corneal Incision on Steep Meridian with Preexisting Astigmatism in Cataract Surgery by Phacoemulsification - Hasan, Mohammad Mahbubul; Begum, Hasiba; Hasan, AKM Rashedul (Community Based Medical Journal, 2023)
A cross-sectional, descriptive study was conducted in the Department of Ophthalmology, Combined Military Hospital (CMH), Dhaka Cantonment, Bangladesh, between November 2017 and May 2018, to assess the keratometric results of clear corneal incision on the steep meridian in patients with preoperative astigmatism during phacoemulsification cataract surgery. After obtaining written informed consent, a total of 40 cataract patients with age ranged between 40 and 70 years were selected. All patients were examined pre- and postoperatively after 1 week and 3 months for evaluation of astigmatism. Keratometry was done by using an autorefractometer and an autokeratometer. Astigmatism was calculated from keratometric data using vector analysis. The mean age of the study participants was 52±9.1 years. Male predominance was observed as male-female ratio was 1.7:1. The change in astigmatism in between pre- and post-operative were 0.44±0.20 in temporal incision group and 0.19±0.00 in superior incision group; both were statistically significant (P<0.001). The difference in mean astigmatism between the groups was 0.375 (P<0.001). Postoperative astigmatism <0.5D was observed in 16(40%) patients when incision was given at temporal site and in 8(20%) patients when incision was given at superior site. Astigmatism was significantly (P<0.05) decreased more when incision given at temporal site in comparison to superior site. Our data suggest that preexisting astigmatism was significantly decreased postoperatively in majority of patients when incision was placed on steep meridian and temporal incision has less surgically induced astigmatism than superior incision. CBMJ 2023 January: Vol. 12 No. 01 P: 27-32